A Post-Master's Advanced Diploma and a MSW Specialization in Social Service Administration: Design, Delivery, and Assessment of Outcomes. Issue 3 (27th May 2017) - Shera, Wes; Bejan, Raluca
ABSTRACT: Many social workers with primarily direct practice experience have been increasingly moving into upper-level administrative roles within their organizations. Unfortunately, many of these new leaders do not have an adequate base of knowledge and skills needed to manage human service organizations. In response to this identified need the Factor-Inwentash Faculty of Social Work in Toronto developed both a post-graduate diploma in social service administration, and a new social service administration specialization within its Master of Social Work (MSW) program. This article describes the design, delivery and evaluation of these initiatives.